Peningkatan Kemampuan Menulis Naskah Drama melalui Pendekatan Kontekstual Berbasis Cerita Rakyat Musi Rawas Siswa Kelas VIII SMP Negeri Pedang - Lasmiyanti, Arie; Sarwono, Sarwit; Gumono, Gumono (Diksa : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2019)
The purpose of this study was to describe the improvement in writing drama scripts through a contextual approach based on the folklore Musi Rawas grade VIII students of SMP Negeri Pedang. This type of research is classroom action research. The data source of this research is VIII grade students of SMP Negeri Pedang in the 2018/2019 academic year, while the research data is the ability to write media-based drama scripts of Musi Rawas folklore. Data collection techniques using test, observation, and documentation techniques. The study was conducted in two cycles, each cycle designed with the details of the activities of each meeting as follows: (1) planning, (2) action, (3) observation, and (4) reflection. Test the validity of the data using triangulation. The results of this study indicate that there was an increase in the ability to write drama scripts for VIII grade students of SMP Negeri Pedang by using a contextual approach based on Musi Rawas folklore. This is indicated by an increase in learning outcomes from cycle 1 to cycle 2. In cycle 1 students who completed 44.5% with enough categories and an increase in cycle 2 with the number of students who completed 86.1% with good categories.